2004
DOI: 10.1103/physreve.69.026413
|View full text |Cite
|
Sign up to set email alerts
|

Confinement and dynamics of laser-produced plasma expanding across a transverse magnetic field

Abstract: The dynamics and confinement of laser-created plumes expanding across a transverse magnetic field have been investigated. 1.06 m, 8 ns pulses from a neodymium-doped yttrium aluminum garnet laser were used to create an aluminum plasma which was allowed to expand across a 0.64 T magnetic field. Fast photography, emission spectroscopy, and time of flight spectroscopy were used as diagnostic tools. Changes in plume structure and dynamics, enhanced emission and ionization, and velocity enhancement were observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
128
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(134 citation statements)
references
References 38 publications
5
128
1
Order By: Relevance
“…However, with a background magnetic field transverse to the blow-off direction, several new phenomena come into play, including plume confinement, plasma instabilities, and the conversion of plasma kinetic to thermal energy. Harilal et al [29] have seen electron heating at the edge of a laser-driven plasma expanding into a magnetic field and have argued that electron cooling can be retarded due to resistive Ohmic heating and adiabatic compression by the magnetic field. Similar conditions appear to be in effect here, though over a larger spatial and temporal scale (see also [30]).…”
Section: Resultsmentioning
confidence: 99%
“…However, with a background magnetic field transverse to the blow-off direction, several new phenomena come into play, including plume confinement, plasma instabilities, and the conversion of plasma kinetic to thermal energy. Harilal et al [29] have seen electron heating at the edge of a laser-driven plasma expanding into a magnetic field and have argued that electron cooling can be retarded due to resistive Ohmic heating and adiabatic compression by the magnetic field. Similar conditions appear to be in effect here, though over a larger spatial and temporal scale (see also [30]).…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25] This capability becomes essential for a hydrodynamic understanding of the plume propagation and reactive scattering. Plasma emission begins on the target surface soon after the laser photons reach the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Rai et al [7] studied the emission properties of LPP from both solid and liquid targets expanding across a magnetic field with the aim of enhancing the sensitivity of the LIBS system. Both Harilal et al [8] and L. Dirnberger et al [9] also studied the expansion of LPP across a magnetic field and observed enhanced emission from ionized species. This was qualitatively explained in terms of a magnetohydrodynamic (MHD) model of the interaction of the moving plasma with the field.…”
Section: Introductionmentioning
confidence: 99%